Detection of multidrug resistance Aeromonas hydrophila in farm raised fresh water prawns (Journal of Advanced Veterinary and Animal Research, 2015)
This  study  was  undertaken  for  isolation, identification  and  determination  of  antibiogram profile of Aeromonas hydrophila in farm raised fresh water  prawn  (Macrobrachium  rosenbergii)  on  five commercial  ghers.  Fresh  water  prawns  (n=25)  were collected from five ghers located at Satkhira, Bagerhat and  Khulna  districts  of  Bangladesh.  Brain  (n=25), muscle  (n=25)  and  intestine  (n=25)  samples  were collected  aseptically  from  fresh  water  prawn  and inoculated  into  alkaline  peptone  (APW)  water  for enrichment  at  37 ?   for  8  h.  Enriched  cultured  was streaked  into  Thiosulfate  Citrate  Bile  Salt  Sucrose (TCBS)  agar  to  isolate  bacteria.  Bacteria  were identified  by  cultural,  Gram  staining,  biochemical properties  and  polymerase  chain  reaction  (PCR) assay.  The  antibiogram  profiles  of  bacteria  were investigated  against  5  commonly  used  antibiotics (Gentamicin,  Cefalexin,  Ampicillin,  Azithromycin and  Ciprofloxacin)  by  disc  diffusion  method. Thirteen  A.  hydrophila  isolates  were  identified  and the  prevalence  of  the  A.  hydrophila  in  fresh  water prawn  was  17.33%.  All  13  (100%)  isolates  were sensitive to Ciprofloxacin, Gentamicin, Azithromycin and resistant to Ampicillin and Cefalexin. The results of  this  study  indicate  that  farm  raised  fresh  water prawn  harbor  multidrug  resistant  A.  hydrophila which  might  causes  public  health  problem  if  enter into human food chain.http://dx.doi.org/10.5455/javar.2015.b120